2021
DOI: 10.1002/ccr3.3982
|View full text |Cite
|
Sign up to set email alerts
|

BRAF‐mutated malignant melanoma with chondrosarcomatous differentiation in inguinal nodal metastasis

Abstract: We report the case of a young woman who developed metastatic melanoma in the inguinal nodal region, which acquired chondrosarcomatous differentiation and preserved the BRAF mutation found in the primary tumor. The patient was treated with a BRAF/MEK inhibitor combination therapy (dabrafenib/trametinib), which was demonstrated to be effective and well‐tolerated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…Nevertheless, this expression is usually weaker than in osteosarcomas [ 40 ]. These tumors tend to occur on acral skin, but various other locations, such as the sun-exposed skin of the face, have been reported [ 41 , 42 , 43 ]. Local traumatism may trigger these lesions, as various authors have reported a history of trauma at the site of osteo-chondroid melanomas [ 42 ].…”
Section: Histological Immunohistochemical and Molecular Features Of P...mentioning
confidence: 99%
“…Nevertheless, this expression is usually weaker than in osteosarcomas [ 40 ]. These tumors tend to occur on acral skin, but various other locations, such as the sun-exposed skin of the face, have been reported [ 41 , 42 , 43 ]. Local traumatism may trigger these lesions, as various authors have reported a history of trauma at the site of osteo-chondroid melanomas [ 42 ].…”
Section: Histological Immunohistochemical and Molecular Features Of P...mentioning
confidence: 99%